Glaciotectonic deformations in the Jammerbugt and glaciodynamic development in the eastern North Sea. (26th August 2016) - Schack Pedersen, Stig A.; Boldreel, Lars Ole
ABSTRACT: The Quaternary geology in the eastern part of the North Sea is characterized by large‐scale glaciotectonic complexes. The northernmost complex is the Jammerbugt Glaciotectonic Complex here addressed, which occupies an area of more than 300 km 2 . It was recently recognized during an investigation of conventional seismic profiles located about 10 km offshore the west coast of northern Denmark. The deformed bedrock includes the main part of the Cretaceous Chalk Group in the North Sea. In the northern part of the complex the detachment surface is situated in Lower Cretaceous greensand about 400 m below sea level. In the central part of the complex, the thrusting ramps the strong reflectors at the base of the Chalk Group and the detachment surface continues in the lower part of the Upper Cretaceous chalk. In the tectonic depression north of the complex, marine and glaciomarine deposits represent the Eemian–Early Weichselian Skærumhede Group, indicating a Saalian age of the glaciotectonic deformation. The balancing of the thrust fault structures shows that the thrust sheets in the tailing end of the complex had their source in the Skagerrak sea. The hole caused by displacement contributed to formation of the Skagerrak depression, i.e . early stage of the Norwegian Trench.